THE INFLUENCE OF HOSPITAL IMAGE SERVICES ON NEED COMMUNITIES IN REGIONAL GENERAL HOSPITAL (RSUD) BAU-BAU CITY - Dahmar Dahmar; Taswin Taswin; Almin Arifudin Osi; Ni'ma Meilani; Adius Kusnan (STIKes Hang Tuah Pekanbaru, 2019)
Data on inpatient visits to the Baubau City General Hospital, in 2015 the number of inpatient visits was 6.518 patients, in 2016 there were 7.023 patients, while in 2017 there were 7.119 patients. This study aims to determine the Effect of Inpatient Service Image on Need Society at the Baubau City General Hospital from the level of service of health workers, health service facilities and infrastructure, and environmental conditions. This type of research is quantitative research with a Cross Sectional approach. The total population is 7.119. The sample in this study were 99 patients who were in the inpatient room at the Baubau City General Hospital. The sampling technique is done by the method of accidental sampling. The results showed that there was an influence on the services of health workers with community needs with a significance value of 0.026, which meant that health care services were smaller than probability values ​​or 0.026 <0.05, health service facilities and infrastructure were smaller than probability values ​​or 0,000 <0.05, environmental conditions are smaller than the probability value or 0.004 <0.05. It can be concluded that there is an influence between the services of health workers on community needs, facilities and infrastructure for health services for the community needs, environmental conditions for the need of the community in the Baubau City general hospital